2021
DOI: 10.3390/ma14092357
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Photonic Thin Films for Solar Irradiation Tuneability Oriented to Greenhouse Applications

Abstract: The world population is growing by 1 billion people every 10 years. There will come a time when there will be more people to feed but less land to grow food. Greenhouses can be the solution to this problem because they provide the highest production yield per m2 and also use less water, provide food safety, and offer high quality. Photosynthetic active radiation (PAR) favors vegetable growth with a specific blue and red light ratio. Thus, increasing the amount of red light improves chlorophyll absorption and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Before making assumptions about the reasons for the positive effect of the PCF, it should be noted that the passing of light through glass coated with luminescent nanopar-ticles was not accompanied by a noticeable increase in the intensity of the visible range. However, in the present work, as well as in a number of other works, an increase in plant productivity was demonstrated [25][26][27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Nanosized particles can act as a protectant against UV owing to their capability to absorb and scatter ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 70%
“…Before making assumptions about the reasons for the positive effect of the PCF, it should be noted that the passing of light through glass coated with luminescent nanopar-ticles was not accompanied by a noticeable increase in the intensity of the visible range. However, in the present work, as well as in a number of other works, an increase in plant productivity was demonstrated [25][26][27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Nanosized particles can act as a protectant against UV owing to their capability to absorb and scatter ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 70%
“…We present a study of WLEDs using organic fluorescent dyes to replace the conventional phosphor. These organic luminescent materials have already been tested as spectral converters in the energy sector (photovoltaics) [23][24][25], in the agrifood sector (greenhouses) [26], and even in the medical sector (ophthalmology) [27] to achieve a specific spectral redistribution. The lighting industry may benefit from these types of materials, which are sustainable, environmentally friendly, and free of geopolitical tensions.…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that tinted semi-transparent PV can actually increase yields for some plants [123]. There is research that has shown spectral shifting materials could also be of use in greenhouses [124][125][126].…”
Section: Case Study Of Red Agrivoltaic Module Experimental Design With a Poscasmentioning
confidence: 99%